Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12864-020-6748-0
|View full text |Cite|
|
Sign up to set email alerts
|

Draft genome sequences of Hirudo medicinalis and salivary transcriptome of three closely related medicinal leeches

Abstract: Background Salivary cell secretion (SCS) plays a critical role in blood feeding by medicinal leeches, making them of use for certain medical purposes even today. Results We annotated the Hirudo medicinalis genome and performed RNA-seq on salivary cells isolated from three closely related leech species, H. medicinalis, Hirudo orientalis, and Hirudo verbana. Differential expression analysis verified by proteomics identified salivary ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 95 publications
0
36
0
Order By: Relevance
“…H. robusta is a leech of the family glossiphoniidae, which is very far from the family hirudinidae [22]. The genome of H. medicinalis in the family hirudinidae was just published during the review period of this study [8,9]. In this study, we reported the genome of W. pigra, another medicinal leech in the family hirudinidae.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…H. robusta is a leech of the family glossiphoniidae, which is very far from the family hirudinidae [22]. The genome of H. medicinalis in the family hirudinidae was just published during the review period of this study [8,9]. In this study, we reported the genome of W. pigra, another medicinal leech in the family hirudinidae.…”
Section: Discussionmentioning
confidence: 90%
“…Its early development has been studied extensively. For another important family hirudinidae, the genome of H. medicinalis has just been published during the review period of this study [8,9]. The family hirudinidae includes medicinal leeches which have been widely utilized in medical procedures for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…The contigs of the H. medicinalis microbiome were generated during a previous study involving the H. medicinalis genome analysis due to the binning procedure [ 16 ]. De novo annotation of the metagenome H. medicinalis allowed us to generate a database of proteins that can serve as a source of AMPs.…”
Section: Resultsmentioning
confidence: 99%
“…The metagenome contigs were retrieved previously in the process of H. medicinalis genome annotation [ 16 ]. Bacterial contig groups were annotated using PROKKA (University of Melbourne, Melbourne, Australia) and GhostKOALA (Kyoto University Bioinformatics Center, Kyoto, Japan) software [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation